Graphitic Carbon Nitride Nanosheets as Co‐reactants for Tris(2, 2′‐bipyridine)ruthenium(II) Electrochemiluminescence. Issue 6 (19th February 2019) - Tian, Libing; Zhao, Panpan; Wei, Jingjing; Chi, Yuwu; Zhou, Shu‐Feng; Chen, Lichan
Abstract: The search for a biocompatible co‐reactant for tris(2, 2′‐bipyridine)ruthenium(II) (Ru(bpy)3 2+ ) electrochemiluminescence (ECL) has attracted broad attention towards extending its application in the biomedical field. This work investigates the co‐reactant effect of graphitic carbon nitride nanosheets (CNNSs) on Ru(bpy)3 2+ ECL. CNNSs enhance the anodic ECL of Ru(bpy)3 2+ through the ECL interaction between Ru(bpy)3 3+ and the reductive intermediate of CNNSs, which are generated by either the direct electroreduction of CNNSs or the chemical/electrochemical oxidation of the amine groups on the CNNSs surface by Ru(bpy)3 3+ . The finding may provide a new avenue for the development of self‐enhanced ECL probes and offer a new insight into revealing the surface feature of CNNSs. Abstract : Helping hand : Graphitic carbon nitride nanosheets act as a co‐reactant to enhance the anodic electrochemiluminescence of Ru(bpy)3 2+ .